Neuroprotection of IGF-1 in neonatal hypoxic-ischemic brain injury through downregulation of FoXO3a-PUMA pathway - Tang, Yanli; Zhong, Rui; Liang, Jiayi; Liu, Shuang; Liu, Wanxia; Liu, Tao; Yuan, Baohong; Jiao, Mengya; Yin, Hui (Frontiers in Cellular Neuroscience, 2025)
Insulin-like growth factor-1 (IGF-1) is a single chain polypeptide hormone that plays an essential role in intrauterine and postnatal growth. Recent studies suggest that IGF-1 and its receptor IGF-1R are involved in the pathogenesis of neurological diseases. Here, we explore the effect of IGF-1 signaling in neonatal hypoxic-ischemic (HI) brain injury and elucidate the underlying mechanisms of action. We found that the expression levels of IGF-1 were markedly enhanced in astrocytes post HI. Delivery of IGF-1 significantly alleviates neonatal brain insult and improves neurobehavioral disorders in neonatal mice after HI challenge. Through binding to IGF-1 receptor (IGF-1R), IGF-1 inhibited the apoptosis of neuronal cells following HI exposure. IGF-1 improved neuronal cell survival and proliferation through activation of phosphorylated AKT signaling. Of note, the protective property of IGF-1 against ischemic neuronal insults was dependent on suppression of the FoXO3a-PUMA signaling pathway. Taken together, these findings suggest that IGF-1 may represent a new neuroprotectant for newborns with hypoxic-ischemic encephalopathy.